Avaliação do estado de hidratação de corredores amadores antes e após uma prova de meia-maratona - Emerson Rodrigues Pereira (2011)
The hydration status of an individual is known to directly influence performance during prolonged activities in warm environments. Unfortunately, the methods for its evaluations are contradictory. The aim of the present study was to determine the hydration status of amateur runners in response to an official road race of 21.1 km and verify if urinary measures and body mass difference are capable to evaluate the acute state of hydration when compared to the Posm. 14 male amateurs runners (29 ±4 y.o., 54.3 ± 5.5 mL.kg-1.min-1) participated in this study and were evaluated before and after the race. Mean environmental data along the race were 25.07 ± 2.13°C dry temperature and 54.7 ± 2.2% relative air humidity. Ingested water volume was ad libitum and was controlled using marked plastic bottles provided at the hydration stations located at 0, 2.5, 5.0, 7.5, 10.5, 14.0, 16.0 e 18.5 km from the start line.Hydration status was assessed using urine specific gravity (GEU), urine osmolality (Uosm), urine sodium and potassium concentrations ([Na+]urine, [K+]urine), plasma volume variation (Äplasma), plasma osmolality (Posm), and plasma sodium ([Na+]plasm) and potassium ([K+]plasm) concentrations. Furthermore, body mass variation (ÄBM)was assessed by comparing body mass immediately prior and after the race.Subjects completed the trial in 111.9 ± 9.5 minutes, consumed 0.82 ± 0.40L (0.45 ±23L.h-1) of water and sweat 2.67 L ± 0.23 (1.44 ± 0.18 L.h-1) during exercise. It wasobserved an increase in Posm (before: 288 ± 4; after: 296 ± 6 mOsm.kg-1 (p<0.01) and[Na+]plasm (before: 136 ± 2; after: 142.5 ± 8.2 mEq.L-1; p<0.05) after the race incomparison with before. This aforementioned increase was accompanied by adecrease in plasma volume (-9,79 ± 4,6%) and BM (1.86 ± 0.40 kg; 2.4 ± 0.39%;p<0.05), indicating a state of hypohydration after the race. (K+)plasma was not differentbetween the moments. However, in urine, only [Na+]urine increased after the race (110± 51 vs 72 ± 54 mEq.L-1, p<0.01), while the GEU, Uosm and (K+)urine remainedunaltered in response to the exercise. No significant correlations were observedbetween Posm and ÄBM, and between Uosm and GEU. Therefore, as GEU and Uosmdid not detect the hypohydration state showed by the Posm, it was concluded that theywere not capable to evaluate the hydration state of the runners after a road race of21.1 km. On the other hand, ÄBM appeared to be an appropriate method fordetecting acute changes on hydration status at the conditions of the present study.